PEREMPUAN DAN BENCANA: MEMBERDAYAKAN POTENSI SOSIAL DAN EKONOMI PEREMPUAN KORBAN BANJIR LAHAR DINGIN MERAPI - Yulianingsih Riswan; Diah Arifika (Jurnal Kawistara, 2012)
This paper investigates the impacts of disaster to women in the nearby area. It specically addresses women experience in post-Merapi eruption in Huntara (Hunian Sementara/Temporary Shelter) of Gempol Jumoyo village, Magelang. The purpose of this paper is to explore women’s role in the disaster and to locate domains where women are mostly affected by it. It draws on a qualitative research conducted to a number of women in the Huntara. Data are collected from observation, in-depth interviews, as well as textual documents. The result of this research paper is that not only the disaster affects economic life of the victims, but also social and cultural dimension of the people. Through an investigation of three domains of women, group, work, and family, this study shows how disaster severely affects human life, as well as exposing the resilience of women in disaster area.